Seismic behavior of plane frame with special-shaped CFST columns, H-shaped steel beams and vertical rib connections. (June 2021) - Yang, Yuanlong; Yang, Weiqi; Tang, Xin; Cheng, Yu
Abstract: The seismic behavior of special-shaped concrete-filled steel tubular (CFST) column to H-shaped steel beam plane frame (SCFSTF) with vertical rib connections was investigated experimentally and numerically in this study. Double-bay two-story SCFSTFs with the scale ratio of 1/2 were tested under constant vertical compressive load and cyclic horizontal loads (or displacements), which is a pseudo static experiment considering the axial load ratio. Based on the experimental results, failure modes, bearing capacity, hysteretic curve, skeleton curve, energy dissipation, ductility, rigidity degradation and strength degradation of SCFSTFs were investigated. As a result, a typical strong column-weak beam failure mode was determined. The degradation in strength and rigidity were minimal and energy dissipation capacity and ductility of frames were adequate, demonstrating excellent seismic performance. Besides, energy dissipation capacity and horizontal resistance were improved with axial load ratio increasing within the parametric range of this test. After the test, a finite element method based on software ABAQUS was carried out to further investigate the seismic performance. The numerical results of skeleton curve, rigidity, yield load, peak load and stress distribution agreed well with the test results. The plastic hinge formation process and ultimate failure mode were further investigated using the finite element model.